The associations of butyrate-producing bacteria of the gut microbiome with diet quality and muscle health. (13th August 2021) - Davis, Jessica A; Collier, Fiona; Mohebbi, Mohammadreza; Pasco, Julie A; Shivappa, Nitin; Hébert, James R; Jacka, Felice N; Loughman, Amy
ABSTRACT: This study aimed to investigate the relationships between diet quality, the relative abundance of butyrate-producing bacteria of the gut microbiome and muscle mass, strength and function. In this cross-sectional study, n  = 490 men (64.4 ± 13.5 years) from the Geelong Osteoporosis Study provided food frequency questionnaire data, from which the Australian Recommended Food Score (ARFS) and Dietary Inflammatory Index (DII) score were calculated. Muscle mass (skeletal muscle index from DXA-derived lean mass), muscle strength (handgrip strength) and muscle function (Timed Up-and-Go test) were measured. Participants provided stool samples for 16S rRNA gene sequencing. There was no evidence of associations between alpha or beta diversity and muscle health measures. A healthier ARFS score was positively associated with the relative abundance of butyrate-producing bacteria ( β 0.09, 95%CI 0.03, 0.15) and a higher (pro-inflammatory) DII score was associated with lower relative abundance of butyrate-producing bacteria ( β −0.60, 95%CI −1.06, −0.15). The relative abundance of butyrate-producing bacteria was positively associated with healthier muscle mass, strength and function; however, these relationships were attenuated in multivariable models. These findings support the role of diet quality in achieving a healthier gut microbiome, however, further evidence is required for a gut-muscle axis in humans.